Co-Existence between Community and Wild Animals among Urban and Suburban Residents in Malaysia - Muslim, Huda Farhana Mohamad; Tetsuro, Hosaka; Shinya, Numata (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
Introduction: The presence of habitats of wild animals and plants in urban areas improves the quality of life for urban dwellers. An increase in interactions between people and wild animals could lead to an increase in human-wildlife conflicts. A decline in direct experience with nature can lead to disaffection of natural environments, and wildlife, and public indifference towards biodiversity conservation. This study measured affective attitudes towards wildlife (i.e., preferences for and willingness to coexist with 22 animal species) and examined the relationships between these attitudes and childhood experiences with nature. Methods: A face-to-face interview was carried out in rapidly urbanizing Malaysia for both urban and suburban 357 adults (age > 20 years old). The questionnaire survey was conducted in three urban towns and three suburban districts. Results: There was a marked variation in Preference and Coexistence scores among the 22 animal species. The animals with the highest Preference scores were insects (e.g., butterfly, dragonfly, firefly, cicada, beetle, and cricket) and squirrels. This study result showed that Malaysian people liked several insects and squirrels, but disliked mammals generally. Mediation analysis, with controlling sociodemographic factors (gender, age and ethnicity), showed that childhood nature experience was positively associated with a preference for wild animals (standardized path coefficient = 0.18; p < 0.001), and the preference had a strong correlation with willingness to coexistence (standardized path coefficient = 0.61; p < 0.001) with the animals. Childhood nature experience, however, had limited effects on willingness to coexist with the animals via preference, particularly for unfavourable animals. These results suggest that preference and willingness scores, even though they were significantly correlated, were different sides of affective attitudes toward animals. Conclusions: Therefore, to promote biodiversity conservation programs, we need strategies to increase the acceptance of wild animals via relevant environmental education and public communication, as well as opportunities for nature activities for children.